Front Cover: A Phthalocyanine‐Based Glutathione‐Activated Photosensitizer with a Ferrocenyl Boron Dipyrromethene Dark Quencher for Photodynamic Therapy (ChemPhotoChem 10/2019). Issue 10 (2nd October 2019) - Shi, Wen‐Jing; Ng, Dennis K. P.; Zhao, Shirui; Lo, Pui‐Chi
Abstract : The Front Cover illustrates the activation of a phthalocyanine‐based photosensitizer through cleavage of the disulfide linker by intracellular glutathione (GSH) and separation from the ferrocenyl boron dipyrromethene based dark quencher. More information can be found in the Article by W.‐J. Shi et al. on page 1004 in Issue 10, 2019 (DOI: 10.1002/cptc.201900115 ).